Implementasi nilai-nilai pancasila dalam kehidupan sosial dan akademik mahasiswa di lingkungan kampus - Avcarina, Aurelya Izza (Maliki Interdisciplinary Journal, 2025)
Pancasila, as the philosophical foundation of Indonesia, plays a vital role in shaping the social and academic life of university students. Its five core principles Divinity, Humanity, Unity, Democracy, and Social Justice serve as moral and spiritual guidelines for developing a generation of young people with integrity and a strong national identity. This study aims to analyze the implementation of Pancasila values within students’ social and academic spheres and to identify the challenges faced in the era of globalization and digital transformation. The research employs a qualitative descriptive method through library research based on scholarly works and indexed academic articles from the State Islamic University of Maulana Malik Ibrahim Malang (2024–2025). The findings reveal that the implementation of Pancasila in universities remains suboptimal. There exists a gap between conceptual understanding and moral practice, reflected in intolerance, declining academic integrity, and weakening national awareness. Revitalizing Pancasila requires strengthening character education, promoting academic role models, fostering digital ethics grounded in humanity, and building synergy among universities, families, and communities to cultivate students who embody Pancasila’s ethical, intellectual, and social justice ideals.